How Do Subnational Governments Contribute to Territorial Development? An Exploratory Analysis of Public Goods and Services Provided by Uruguay's Departmental Governments - Adrián Rodríguez-Miranda; Camilo Vial (RPER, 2026)
This article analyzes the contribution of subnational governments to territorial development through the study of public goods and services provided by Departmental Governments in Uruguay. Although they execute only around 10% of the national budget, they hold significant responsibilities in areas such as land use, local transportation, and primary healthcare. However, their actual capacity to influence development varies across departments. Based on the Regional Development Index for Uruguay, this study develops a pilot methodology to construct the Local Provision of Public Goods and Services Index, composed of two dimensions: the degree of autonomy with which Departmental Governments provide public goods and services, and the budgetary priority assigned to different dimensions of development. The methodology is applied to two case studies—Rivera and San José—selected due to their differing levels of development. The results show a strong correlation between higher levels of autonomy in local public goods and services provision and improvements in territorial development indicators, particularly in social cohesion and economic activity. It is concluded that effective autonomy, even with limited resources, could be a key factor in promoting more equitable territorial development. The approach requires further validation in future research.